Specifications of Sugar Cane Varieties Based on Land Characteristic and Typology - Basuki Basuki; Vega Kartika Sari (The University of Lampung, 2024)
The productivity of sugarcane is decreasing and there are more and more varieties in circulation. The decrease in productivity is caused by the incompatibility of each variety of land typology. The purpose of this research is to arrange the right varieties in increasing the productivity of sugarcane. The research method is surveying and matching. Parameters used include soil texture, land type conditions, soil drainage conditions, and rainfall. Based on the research results, the total working area of 11,866.81 ha was divided into 4 land typologies, namely BHJ with an area of 2,910.95 hectares (24.53%), BPJ with an area of 2,047.44 hectares (17.25%), RHL an area of 471.12 hectares (3.97%), RPL area of 1,527.01 hectares (12.87%). Based on land typology the suitability of BHJ varieties of sugarcane suitable varieties PSMLG 1 AGRIBUN, VMC76-16, NX03, PS921, PSJT941, PSDK923; BPJ land typology of suitable varieties Cenning, VMC71-238, PA0218, NX01, Kentung, AASAgribun, PSJT 941, PSDK923, PSBK051, NX02; RHL land typology of suitable varieties PSKA 942, PA028, PSBK061, VMC76-16, AMS Agribun, ASA Agribun, PSJT941, NXI4T, MOJO01, Bululawang; RPL land typology of suitable varieties PS881, TLH02, PSKA 942, PSBK061, PS091, PSJK922, VMC86-550, PS862, PS851, PSCO902, Kidang Kencana, PS882, PS092, PS865, PS864, NXI4T, Bululawang. Keywords: Soil drainage, Soil texture, Soil type, Soil typology, Sugarcane varieties.